Perlindungan Konsumen Persepktif Hukum Ekonomi Syariah - Hotman; Handayani, Wiwik (Institut Agama Islam Negeri Metro, 2022)
The principles of Islamic economics are based on Islamic values that govern the behavior of both business actors and consumers, setting boundaries for transactions. One key distinction between Islamic economics and conventional economics lies in the guiding principles derived from Islamic law, particularly the Quran and Hadith, which ensure that economic activities comply with Sharia. Indonesia’s economic system should be aligned with both government regulations and Islamic law to create harmony between the two legal systems, promoting ethical behavior, honesty, and preventing harm to others. Conflicts often arise when actions deviate from established rules, highlighting the need for legal regulations that protect consumers and deter businesses from exploiting customers or manipulating goods for profit. Experts in economics should be actively involved in managing Indonesia's economy to ensure sustainable growth and prevent economic decline. The potential for Indonesia's economic development is significant, and strategic efforts must be intensified to support this growth. A well-regulated framework, with clear boundaries and strict sanctions, will prevent unethical practices, ensuring that economic activities are fair, just, and beneficial for all, ultimately contributing to Indonesia's economic progress.